1983
DOI: 10.2307/3586618
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Composition Scoring Techniques, Objective Measures, and Objective Tests to Evaluate ESL Writing Ability

Abstract: The evaluation of writing ability among both L1 and L2 students has become increasingly important in recent years because the results of such evaluation are used for a variety of administrative, instructional, and research purposes. Classroom teachers, in particular, because they want to use these results to help improve, influence, refine, and shape their students' attained writing ability, have specific concerns regarding the various methods of writing assessment available. Additional concerns, especially of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 21 publications
0
45
0
1
Order By: Relevance
“…According to Stiggins, Richard, Nancy, and Bridgeford (as cited in Perkins, 1983) "Holistic scoring calls for the reader to rate overall writing proficiency on a single rating scale, (but) analytic scoring breaks performance down into component parts (e.g. organization, wording, idea)" (p. 652).…”
Section: Baleghizadeh and Hajizadehmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Stiggins, Richard, Nancy, and Bridgeford (as cited in Perkins, 1983) "Holistic scoring calls for the reader to rate overall writing proficiency on a single rating scale, (but) analytic scoring breaks performance down into component parts (e.g. organization, wording, idea)" (p. 652).…”
Section: Baleghizadeh and Hajizadehmentioning
confidence: 99%
“…Bacha (2001) confirmed that adopting either of these techniques depended on the purpose of writing in EFL programs. She maintained that to provide learners with more specific feedback, analytic scoring would be more appropriate since holistic scoring tends to be highly subjective and lacks internal consistency due to shifting standards (Perkins, 1983). Other scholars such as Hamp-Lyons (1995) have pointed out that "holistic scoring system is a closed system" (p. 760) and no one can have access to points for different parts since the raters do not have a certain criterion for scoring a piece of writing.…”
Section: Baleghizadeh and Hajizadehmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the raters may pay less attention to the written text as a whole by simply letting the questions lead them through the essay, causing text features to be isolated from the context (Perkins, 1983). Secondly, it is questionable whether the construct of writing ability can be 'captured' by a finite set of questions, meaning there is no guarantee that all relevant questions are being asked and, subsequently, that all relevant features of writing ability are assessed.…”
Section: Assessing Writing In a Large-scale Assessmentmentioning
confidence: 99%